Towards free-standing graphane: atomic hydrogen and deuterium bonding to nano-porous graphene. (22nd October 2020) - Abdelnabi, Mahmoud Mohamed Saad; Blundo, Elena; Betti, Maria Grazia; Cavoto, Gianluca; Placidi, Ernesto; Polimeni, Antonio; Ruocco, Alessandro; Hu, Kailong; Ito, Yoshikazu; Mariani, Carlo
Abstract: Graphane is formed by bonding hydrogen (and deuterium) atoms to carbon atoms in the graphene mesh, with modification from the pure planar sp 2 bonding towards an sp 3 configuration. Atomic hydrogen (H) and deuterium (D) bonding with C atoms in fully free-standing nano porous graphene (NPG) is achieved, by exploiting low-energy proton (or deuteron) non-destructive irradiation, with unprecedented minimal introduction of defects, as determined by Raman spectroscopy and by the C 1s core level lineshape analysis. Evidence of the H- (or D-) NPG bond formation is obtained by bringing to light the emergence of a H- (or D-) related sp 3 -distorted component in the C 1s core level, clear fingerprint of H–C (or D–C) covalent bonding. The H (or D) bonding with the C atoms of free-standing graphene reaches more than 1/4 (or 1/3) at% coverage. This non-destructive H-NPG (or D-NPG) chemisorption is very stable at high temperatures up to about 800 K, as monitored by Raman and x-ray photoelectron spectroscopy, with complete healing and restoring of clean graphene above 920 K. The excellent chemical and temperature stability of H- (and D-) NPG opens the way not only towards the formation of semiconducting graphane on large-scale samples, but also to stable graphene functionalisation enabling futuristic applications in advanced detectors for the β -spectrum analysis.